Impact of coronavirus disease 2019 epidemics on prevention and care for HIV and other sexually transmitted infections. (1st May 2022) - de Lazzari, Elisa; Martínez-Mimbrero, Alejandra; Chivite, Iván; González-Cordón, Ana; Mosquera, Maria M.; Laguno, Montserrat; Costa, Josep; Bosch, Jordi; Blanco, Jose L.; Álvarez-Martinez, Miriam; Ugarte, Ainoa; Inciarte, Alexy; et al.
Abstract : Objective: To assess the impact of coronavirus disease 2019 (COVID-19) epidemics on the prevention and care for HIV and other sexually transmitted infections at a major reference centre providing preventive and clinical services in Catalonia, Spain. Design: We retrospectively compared anonymized clinical and laboratory data from March to December 2020 vs. 2019. Methods: Monthly clinical data on HIV preexposure and postexposure prophylaxis users and on adults with HIV infection were retrieved from the administrative hospital database. Monthly tests for HIV, hepatitis B and C, Treponema pallidum, Neisseria gonorrhoeae, and Chlamydia trachomatis, and plasma lipids and glucose were recovered from the laboratory database. Results: There were less (↓28%, P   =  0.003) but more advanced (mean CD4 + cells/μl 305 vs. 370, P   <  0.001) HIV infections and more gonorrhoea (↑39%, P   <  0.001) and chlamydia (↑37%, P   <  0.001) infections in 2020 vs. 2019. In people with HIV, rates of HIV RNA less than 50 copies/ml remained stable (11 vs. 11%, P   =  0.147) despite less scheduled visits (↓25%, P   <  0.001). However, they had less antiretroviral prescription changes (↓10%, P   =  0.018), worse plasma lipids [mean total cholesterol 190 vs. 185 mg/dl, P   <  0.001;mean low-density lipoprotein (LDL) cholesterol 114 vs. 110 mg/dl, P   <  0.001; mean triglycerides 136 vs. 125 mg/dl, P   <  0.001; mean high-density lipoprotein (HDL) cholesterol 47 vs. 48 mg/dl, P   =  006], and an excess of mortality (↑264%, P   =  0.006) due in great part not only to COVID-19 but also to other causes. Conclusion: In our setting, COVID-19 epidemics was associated with an increase in some prevalent sexually transmitted infections, with less but more advanced HIV infections, and with worse nonvirologic healthcare outcomes and higher mortality in people living with HIV.